2008
DOI: 10.1007/s00227-008-1059-z
|View full text |Cite
|
Sign up to set email alerts
|

Is Hippolyte williamsi gonochoric or hermaphroditic? A multi-approach study and a review of sexual systems in Hippolyte shrimps

Abstract: Sexual systems vary considerably among caridean shrimps and while most species are gonochoric, others are described as sequential protandric hermaphrodites or simultaneous hermaphrodites with an early male phase. At present, there is confusion about the sexual system exhibited by several species mostly because those studies attempting to reveal their sexual system draw inferences solely from the distribution of the sexes across size classes. Here we investigated the sexual system of the shrimp Hippolyte willia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
21
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 48 publications
6
21
1
1
Order By: Relevance
“…Finally, these results (based on 176 males studied without any signs of sex reversal), altogether with our previous studies (Cobos et al 2005;Manjón-Cabeza et al 2009), support the existence of a gonochoric structure of the studied population of H. inermis (from Zostera beds) like has been described recently in other species of the same genus such as H. williamsi Schmitt 1924 H. obliquimanus Dana 1852 (Espinoza-Fuenzalida et al 2008;Terossi et al 2008).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Finally, these results (based on 176 males studied without any signs of sex reversal), altogether with our previous studies (Cobos et al 2005;Manjón-Cabeza et al 2009), support the existence of a gonochoric structure of the studied population of H. inermis (from Zostera beds) like has been described recently in other species of the same genus such as H. williamsi Schmitt 1924 H. obliquimanus Dana 1852 (Espinoza-Fuenzalida et al 2008;Terossi et al 2008).…”
Section: Discussionsupporting
confidence: 89%
“…However, two different studies from our laboratory have found no evidence for hermaphroditic sexuality in adult specimens of this species after a careful examination of the morphology of the reproductive structures (Cobos et al 2005) and an exhaustive study of its population structure and absolute growth (Manjón-Cabeza et al 2009). Recent studies regarding the reproductive system in other species of Hippolyte have not found either any cases of sex reversal (Espinoza-Fuenzalida et al 2008;Terossi et al 2008), and consequently they were described as gonochoristic species.…”
Section: Introductionmentioning
confidence: 99%
“…The location of gonopores on the third pair of pereiopods in females and on the fifth pair of pereiopods in males is in line with the previous literature on caridean shrimps (Mascetti et al 1997; Espinoza-Fuenzalida et al 2008; Terossi et al 2008; Tóth and Bauer 2007, 2008; Manjon-Cabeza et al 2011). The shape and structure of male gonopores in our study are similar to those observed by Espinoza-Fuenzalida et al (2008) in Hippolyte williamsi . Female gonopores in H. inermis are characterised by the presence of a flap, just distal to the gonopore opening, at the proximal end of the third pair of pereiopod coxae.…”
Section: Discussionsupporting
confidence: 89%
“…A gonochoristic sexual system has been demonstrated in congeneric species viz. H. williamsi (Espinoza-Fuenzalida et al 2008), H. obliquimanus (Terossi et al 2008), and H. niezabitowskii (Manjon-Cabeza et al 2011). As expected, the number of females in the treatment CTRL+ was higher than in the CTRL−, indicative of the process of sex reversal triggered by the apoptogenic compounds present in the CTRL+ food (Zupo and Messina 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Most caridean shrimps are gonochoric, with individuals in a population producing only male or female gametes during their entire life. Well-studied examples include Rhynchocinetes typus (Correa et al, 2000), Hippolyte obliquimanus (Terossi et al, 2008), Pontonia margarita (Baeza, 2008a), and Hippolyte williamsi (Espinoza-Fuenzalida et al, 2008). The second most common sexual system is protandry.…”
mentioning
confidence: 99%